2017
DOI: 10.5541/eoguijt.324160
|View full text |Cite
|
Sign up to set email alerts
|

Energy and Exergy Analysis of a Pre-distillation Unit

Abstract: Energy and exergy balances were evaluated for the pre-distillation unit (Un-0100) of an aromatics plant from a Portuguese refinery. The main objective of the study was to find out the relevant thermal energy losses in order to implement energy recovery procedures, without questioning the operating processes of the plant. In its overall analysis, the Un-100 obtained an energy efficiency of 13.4% and an exergy efficiency of 2.3%. The equipment that has higher energy losses in this unit is the air coolers, repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Several scholars conducted assessments on the energy and exergy efficiencies within diverse agricultural productions such as onion (Kaveh et al, 2021), green peas (Kaveh et al, 2020), potato (Golpour et al, 2020), wheat (Yan et al, 2023), cantaloupe (Zadhossein et al, 2023), water yam (Okunola et al, 2023) and vermicelli (Kumar et al, 2023). Vilarinho et al (2017) carried out an evaluation on the pre-distillation unit by analyzing its energy and exergy. They found that the energy and exergy efficiency of this unit were 13.40% and 2.30%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Several scholars conducted assessments on the energy and exergy efficiencies within diverse agricultural productions such as onion (Kaveh et al, 2021), green peas (Kaveh et al, 2020), potato (Golpour et al, 2020), wheat (Yan et al, 2023), cantaloupe (Zadhossein et al, 2023), water yam (Okunola et al, 2023) and vermicelli (Kumar et al, 2023). Vilarinho et al (2017) carried out an evaluation on the pre-distillation unit by analyzing its energy and exergy. They found that the energy and exergy efficiency of this unit were 13.40% and 2.30%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Song et al, [9] employed extended exergy analysis to investigate a typical cement production chain in China. Vilarinho et al, [10] appraised exergy and energy analysis for a pre-distillation unit (Un-0100) of an aromatics plant from a Portuguese refinery. Navarro et al, [11] evaluated the exergetic performance of Amine Treatment Refinery Unit in Colombia.…”
Section: Introductionmentioning
confidence: 99%